EFFECT OF STARVATION AND REPEEDING ON TISSUE PROXIMATE ANALYSIS OF HEPATIC AND MUSCULAR TISSUES OF TIL API A MOSSAMBICA (PETERS) - Moorthy, C V Narasimha; Murthy, V Krishna; Reddy, G Vemananda; Haranath, V Bhaskara; Reddanna, P; Govindappa, S (Indian Journal of Fisheries, 2011)
starvation in Tilapia mossambica (Peters) induced higher depletion of carbohydratereserves in all the tissues. While liver and red muscle showed higherlipoiysis, the white mwscte had higher proteolysis. The refeeding process resultedin replenishment of tissue reservs in white muscle, while those of liver and redmuscle were at lower level than normal, suggesting the possibility of impairmentof synthetic activities in liver and red muscle after prolonged stairvation. The carbohydratesynthetic efficiency in white muscle seem to be considerably elevatedon refeeding. The lipid reserves of all the tissues were depleted even afterrefeeding and he'nce the course of stairvation and refeeding was envisaged todecrease the tissue fat depots